1993
DOI: 10.1039/c39930001522
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal-carbonyl, -hydrido and -η-cyclopentadienyl derivatives of the fullerene C60

Abstract: Monoadduct derivatives of the fullerene c60, namely [Fe(C0)4(q2-C60)], [ M O ( T ~C ~H ~R ) ~( ~~-C ~~) ] (R = H, Bun), [Ta(q2-C5H5)2(~2-C60)H] and [Rh(Ph3P)2(Co)(q2-C6~)H], are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 8 publications
1
33
0
Order By: Relevance
“…Recently, the formation of fullerene-based organometallic compounds suggests the new forms of materials can be synthesized because the fullerenes may prove to be highly versatile ligands due to their intriguing topography and aromaticity. [3][4][5][6] However, the nature of the metal-fullerene interface has scarcely been revealed.…”
mentioning
confidence: 99%
“…Recently, the formation of fullerene-based organometallic compounds suggests the new forms of materials can be synthesized because the fullerenes may prove to be highly versatile ligands due to their intriguing topography and aromaticity. [3][4][5][6] However, the nature of the metal-fullerene interface has scarcely been revealed.…”
mentioning
confidence: 99%
“…Although an x-ray determined structure of II has not been reported in the literature, the ir spectrum at room temperature 15 shows four infrared active CO stretching modes ͑in addition to an unresolved shoulder at 2045.8 cm Ϫ1 ͒. These four modes are shifted by 41.8Ϯ4.2 cm Ϫ1 from the four bands reported by Green et al for I, 12 and leave little doubt concerning the C 2v point group symmetry of both molecules. In II, as in the title compound, the Fe͑CO͒ 4 fragment is ligated to a single CC double bond along a pseudotwo-fold symmetry axis.…”
Section: Resultsmentioning
confidence: 68%
“…[8] About a decade ago, Green et al reported the first C 60 derivatives of a metallocene, namely, [MoA C H T U N G T R E N N U N G (h 5 -C 5 H 4 R) 2 A C H T U N G T R E N N U N G (h 2 -C 60 )] (R = H, nBu). [9] They also proposed that such metallocenes may bond to C 60 at one of its 30 equivalent double bonds, which occur at the fusion of two six-membered rings. However, to the best of our knowledge, no other experimental data for such reactions, or the species involved, have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%